2013
DOI: 10.1007/s12010-013-0386-9
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormone Supplementation Significantly Increases Growth of Chlamydomonas reinhardtii Cultivated for Biodiesel Production

Abstract: Cultivation is the most expensive step in the production of biodiesel from microalgae, and substantial research has been devoted to developing more cost-effective cultivation methods. Plant hormones (phytohormones) are chemical messengers that regulate various aspects of growth and development and are typically active at very low concentrations. In this study, we investigated the effect of different phytohormones on microalgal growth and biodiesel production in Chlamydomonas reinhardtii and their potential to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(89 citation statements)
references
References 33 publications
4
78
2
1
Order By: Relevance
“…Earlier study reported ABA functioned as a stress molecule in cyanobacteria under salt stress [53] and under salt, osmotic, oxidative, drought and nutrient stresses in unicellular eukaryotic algae [54][55][56][57][58]. The superiority of ABA in promoting lipid biosynthesis was also reported by Park et al [27], where ABA-treatment favored energy storage in the form of either starch or lipid. However, ABA had little effect on algal growth in our results.…”
Section: The Lipids and High Value Pufas Analysismentioning
confidence: 60%
“…Earlier study reported ABA functioned as a stress molecule in cyanobacteria under salt stress [53] and under salt, osmotic, oxidative, drought and nutrient stresses in unicellular eukaryotic algae [54][55][56][57][58]. The superiority of ABA in promoting lipid biosynthesis was also reported by Park et al [27], where ABA-treatment favored energy storage in the form of either starch or lipid. However, ABA had little effect on algal growth in our results.…”
Section: The Lipids and High Value Pufas Analysismentioning
confidence: 60%
“…The biomass productivity of P. kessleri obtained for the concentration of 10 -5 M IAA was 0.83 and 0.63 g l -1 , respectively, for the photoperiod and continuous illumination. Park et al (2014) examined the effect of various concentrations of IAA on biomass production in Chlamydomonas reinhardtii. They reported that the ca.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous auxin increases the growth rate of algae such as Chlorella vulgaris, Chlorella sorokiniana, Chlamydomonas reinhardtii, Haematococcus pluvialis, Pleurochrysis carterae, and Phaeodactylum tricornutum (Lu and Xu, 2015;Park et al, 2014;Piotrowska-Niczyporuk and Bajguz, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the signaling pathway components are not present in basal early-diverging lineages of the Streptophyta and/or other algal lineages (De Smet et al 2010, Lu andMori et al 2017) making it less likely that a phytohormone function could have been inherited from a common unicellular ancestor. Nonetheless, evidence for phytohormone function in unicellular algae is beginning to accumulate, such as the role of abscisic acid and auxins in regulation of growth in unicellular green algae and diatoms ( Kobayashi et al 1997, Yoshida et al 2004, Park et al 2013, Lu et al 2014, Amin et al 2015. This is consistent with the hypothesis that hormones such as auxin might have served initially as growth-regulating hormones or pheromones in unicellular ancestors predating the advent of multicellularity (Cooke et al 2002, Bogaert et al 2013).…”
Section: Endogenous Signalingmentioning
confidence: 99%